Medical Negligence Dispute Settlement in Indonesia - Deri Mulyadi1 , Elwi Danil2 , Wila Chandrawila3 , Kurnia Warman2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The doctor-patient relationship has a specificity that distinguishes it from the business actor relationship.Malpractice is a very general term. Medical malpractice, medical negligence, and medical risk are notregulated in Indonesia and requires medical knowledge to understand them. This is where the difficulty ofproving negligence and medical risk in solving medical negligence disputes. Medical negligence disputes inIndonesia are settled by litigation (criminal and civil) and non-litigation. Non-litigation medical negligencedispute settlement is a breakthrough in resolving medical negligence disputes in Indonesia, namely mediationand the Indonesian Honorary Medical Disciplinary Council or Majelis Kehormatan Disiplin KedokteranIndonesia (MKDKI). This study revealed that there are no clear rules regarding medical negligence, medicalrisk, and medical dispute resolution to produce identical rules based on structure, substance, and culture.The settlement of medical negligence disputes through mediation is an alternative in resolving medicalnegligence disputes in Indonesia to allow for legal certainty and legal protection for doctors and patients.